Зависимость диэлектрической проницаемости кристаллизующейся фазы стеклокерамики от времени спекания - Dmitriyev, M. V.; Yerimichoy, I. N.; Panov, L. I. (PE "Politekhperiodika", Book and Journal Publishers, 2010)
The paper deals with computing technique of effective dielectric permittivity of a crystobalite formed in glass-ceramic body by means of measured dielectric permittivity of glass-ceramic composite. Dependence of the calculated parameter from the time of crystallization is found.